دور التقارير المالية المرحلية في تحسين ملائمة المعلومات المحاسبية دراسة حالة مؤسسة سونطراك - بالقط, مريم (جامعة الوادي - University of Eloued, 2023)
information for institutions and their commitment to their preparation. A field study was conducted in three branches of the National Energy Company (Sonatrach), using a questionnaire to gather opinions from personnel in these branches. The study employed a descriptive approach to analyze the concepts of interim financial reports and accounting information appropriateness, and a statistical method using the (SPSS) software to test hypotheses. The results indicated a high level of commitment by Sonatrach to preparing interim financial reports and a positive impact of these reports on improving accounting information appropriateness
The role of interim financial reports in improving the adequacy of accounting information: Sonatrach case study
مقال
Keywords: تقارير مالية مرحلية؛ معلومات محاسبية؛ اتخاذ القرار؛ مؤسسة سوناطراك; Interim Financial Reports; Accounting Information; Making Decision; Sonatrach institution